Soundscape in religious historical buildings: a review - Zhang, Dongxu; Shan, Yue; Chen, Xinyi; Wang, Zixia (Heritage science, 2024)
Over the past decade, a substantial body of research exploring soundscapes in religious historical buildings has emerged, yet a comprehensive summary of this work is lacking. This paper selects 74 typical studies of soundscapes in religious historical buildings published between 2011 and 2022 to conduct quantitative statistics and visualization analysis from a bibliometric perspective. The selected literature is categorized based on the type of religious building, Christian, Islamic, or Buddhist. The literature is further segmented according to the research subject, including sound field studies, sound analyses, and evaluations of the acoustic environment. The research methods employed are also differentiated and include sound field measurements, acoustic simulations, questionnaires and auralization procedures. The analysis reveals pronounced disparities in research foci depending on the type of religious historical building. For instance, studies on the soundscape in Christian churches tend to focus on objective sound field attributes and frequently employ sound field simulations to analyse the acoustic parameters of diverse church spaces and materials. Conversely, research on the soundscape in Islamic mosques prioritizes speech intelligibility and acoustic comfort, while studies of the soundscape of Buddhist temples gravitate towards the impact of natural and religious sounds on individuals. This paper anticipates the future direction of soundscape research on religious historical buildings. Graphical Abstract